The factors affecting economic growth in Korea Republic / Muhammad Azmi Mahamood - Mahamood, Muhammad Azmi (Faculty of Business and Management, 2018)
This study tries to investigate the relationship between economic growth and independent variables, such as government expenditure, savings rate, and inflation rate at Korea Republic. Secondary data is obtained from 1987 to 2016. By obtaining data each year, the data is collected from the World Indicator database data and OECD data. On the other hand, the technique used to estimate the model is Ordinary Least Square (OLS). The results show that factors affecting economic growth in Korea through government expenditure, savings rates and inflation rates are able to influence those that have a direct and statistically significant relationship to economic growth. However, one of the variables shows its own results with the expected sign. As predicted by theory, inflation actually has a negative impact on economic growth. In other words, when inflation increases, there is a decline in purchasing power where it will slow down economic growth. However, this study investigates inverse results by comparing with the inserted investigation. While this study has some limitations such as lack of data, journals, etc., then the proposal has been proposed to future researchers. Regardless of the limitations this study applies to governments, policy makers, and even macroeconomics.